Potensi Makanan Tradisional Sebagai Daya Tarik Wisata Kuliner Di Kabupaten Karo - Bobby Rahman (Politeknik Pariwisata Medan, 2023)
This study aims to explore the potential of traditional food as a culinary tourism attraction in Karo Regency. Karo Regency, located in North Sumatra, Indonesia, has a rich cultural and culinary heritage. Traditional Karo food has a unique taste, uses local ingredients, and has a distinctive processing technique. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with traditional food stall owners, culinary experts, and tourism officers in Karo District. Participatory observation was carried out in the process of preparing and serving traditional food to gain an in-depth understanding of processing techniques, raw materials, and the uniqueness of traditional food recipes. The results of this study indicate that traditional Karo food has great potential as a culinary tourism attraction. The unique taste, use of local ingredients, and unique processing techniques are attractive factors for tourists who want to taste an authentic culinary experience. Owners of traditional food stalls and culinary entrepreneurs in Karo Regency are also aware of this potential and have developed various innovations in the presentation and promotion of traditional food. Although the potential for traditional Karo food as a culinary tourism attraction is very promising, there are still some challenges that need to be overcome. These challenges include accessibility issues, ineffective promotion, and protection of intellectual property related to traditional food processing recipes and techniques.